Mental Experiences in Wild Animals: Scientifically Validating Measurable Welfare Indicators in Free-Roaming Horses - Harvey AM; Beausoleil NJ; Ramp D; Mellor DJ (MDPI (Basel, Switzerland), 2023)
The mental experiences of animals are what characterises their welfare status. The Five Domains Model for assessing welfare aligns with the understanding that physical and mental states are linked. Following measurement of indicators within each of the four physical/functional Domains (1. Nutrition; 2. Physical environment; 3. Health; and 4. Behavioural interactions), the anticipated negative or positive affective consequences (mental experiences) are cautiously inferred and assigned to Domain 5. Those inferences derive credibility from validated knowledge of the underlying systems of physiology, neurophysiology, neuroethology and affective neuroscience. Any indicators used for assessing welfare need to be scientifically validated. This requires, firstly, evidence of the links between a measurable/observable indicator and the physical/functional impact (in Domains 1 to 4), and secondly, a demonstrable relationship between the physical/functional impact and the mental experience it is inferred the indicators reflect (in Domain five). This review refers to indicators of physical/functional states in Domains 1 to 4, which have been shown to be measurable in free-roaming wild horses, and then evaluates the scientific evidence linking them to inferred mental experiences in Domain 5. This is the first time that the scientific evidence validating a comprehensive range of welfare indicators has been synthesised in this way. Inserting these indicators into the Five Domains Model enables transparently justifiable assessment and grading of welfare status in free-roaming horses.
Keywords: Five Domains Model; affective state; free-roaming horse; horse; mental experience; scientific support; validation; welfare assessment; welfare indicators; wild animal; wild horse; wildlife